Public-Private Collaboration on Productive Development Policies in Colombia - Marcela Eslava Mejía; Marcela Meléndez Arjona; Guillermo Perry (Inter-American Development Bank (IDB), 2014)
This Working Paper analyzes the institutions that shape public-private collaboration for the design and implementation of productive development policies in Colombia. These policies are increasingly designed in the context of formal institutions and venues, with public-private collaboration being a pillar of that formal design. This paper focuses on two specific case studies: the Private Council for Competitiveness and its role in the National Competitiveness System and the Productive Transformation Program. Both suggest that public-private collaboration has contributed to the continuity of productive development policies across the country. Public-private collaboration has also played a significant part in achievements such as overcoming specific government failures and developing private organizational capabilities. Thus, a central message of this paper is that formal institutions have an important potential to advance adequate productive development policies.
hdl:11319/6411
Keywords: O43; D71; D78; L52; 330; Public-private collaboration; Productive development; Colombia